(untitled) (Canada, 2000)
This report summarizes signification lipid degradation in fish muscle during refrigerated and frozen storage is due to enzymatic hydrolysis and leads to both a decrease in phospholipids,...
Keywords: Seafood,Thức ăn hải sản